Can Women Maintain Their Strength Performance Along the Menstrual Cycle? - Florent Osmani; Danel Terán-Fernández; Sergio Alonso-Pérez; Santiago A. Ruiz-Alias; Felipe García-Pinillos; Carlos Lago-Fuentes (Applied Sciences)
This study aimed to explore the effect of the menstrual cycle (MC) phases (i.e., early follicular phase [EFP], late follicular phase [LFP], and mid-luteal phase [MLP]) on the repetitions performed to momentary failure in back squat and bench press exercises, as well as to determine subsequent fatigue (i.e., change in countermovement jump [CMJ], perceived effort, and muscle soreness). Twelve physically active eumenorrheic women performed a back squat and bench press set to momentary failure at 80% of the one-repetition maximum during the EFP, LFP, and MLP. The results revealed that subjects were able to perform 2.2 [0.2 to 4.2] more repetitions in the LFP with respect to the EFP for the back squat exercise (p = 0.009), but no significant differences were observed for the bench press (p = 0.354). The EFP displayed a larger CMJ height drop (−0.86 [−1.71 to −0.01] cm) with respect to the LFP (0.01 [−0.57 to 0.58] cm) and the MLP (−0.36 [−1.15 to 0.43] cm). Neither the perceived effort of each set to failure nor the resulting muscle soreness differed between MC phases. Therefore, practitioners should be aware that the MC could condition the repetitions available to momentary failure and the resulting allostatic load.